Induced Pluripotent Stem Cell-Derived Brain Endothelial Cells as a Cellular Model to Study Neisseria meningitidis Infection - Martins Gomes, Sara F.; Westermann, Alexander J.; Sauerwein, Till; Hertlein, Tobias; Förstner, Konrad U.; Ohlsen, Knut; Metzger, Marco; Shusta, Eric V.; Kim, Brandon J.; Appelt-Menzel, Antje; Schubert-Unkmeir, Alexandra (Frontiers in Microbiology, 2019)
Meningococcal meningitis is a severe central nervous system infection that occurs when Neisseria meningitidis (Nm) penetrates brain endothelial cells (BECs) of the meningeal blood-cerebrospinal fluid barrier. As a human-specific pathogen, in vivo models are greatly limited and pose a significant challenge. In vitro cell models have been developed, however, most lack critical BEC phenotypes limiting their usefulness. Human BECs generated from induced pluripotent stem cells (iPSCs) retain BEC properties and offer the prospect of modeling the human-specific Nm interaction with BECs. Here, we exploit iPSC-BECs as a novel cellular model to study Nm host-pathogen interactions, and provide an overview of host responses to Nm infection. Using iPSC-BECs, we first confirmed that multiple Nm strains and mutants follow similar phenotypes to previously described models. The recruitment of the recently published pilus adhesin receptor CD147 underneath meningococcal microcolonies could be verified in iPSC-BECs. Nm was also observed to significantly increase the expression of pro-inflammatory and neutrophil-specific chemokines IL6, CXCL1, CXCL2, CXCL8, and CCL20, and the secretion of IFN-γ and RANTES. For the first time, we directly observe that Nm disrupts the three tight junction proteins ZO-1, Occludin, and Claudin-5, which become frayed and/or discontinuous in BECs upon Nm challenge. In accordance with tight junction loss, a sharp loss in trans-endothelial electrical resistance, and an increase in sodium fluorescein permeability and in bacterial transmigration, was observed. Finally, we established RNA-Seq of sorted, infected iPSC-BECs, providing expression data of Nm-responsive host genes. Altogether, this model provides novel insights into Nm pathogenesis, including an impact of Nm on barrier properties and tight junction complexes, and suggests that the paracellular route may contribute to Nm traversal of BECs.